Hydrodynamics of Swirled Film Motion - A. M. Volk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of the paper is to investigate stationary laminar axial symmetric motion of a viscous liquid film on an internal wall of a vertical cylinder under influence of the swirled gas flow. The exact self-similar solution of Navier - Stokes equations for axial and tangential speed components has been obtained. Hydrodynamic characteristics of the film motion and analytical conditions for possible motion regimes have been found.